The martyrs of Japan : publication history and Catholic missions in the Spanish World (Spain, New Spain, and the Philippines, 1597-1700) - Roldán-Figueroa, Rady (Studies in the history of Christian traditions, 2021)
"In The Martyrs of Japan, Rady Roldán-Figueroa examines the role that Catholic missionary orders played in the dissemination of accounts of Christian martyrdom in Japan. The work combines several historiographical approaches, including publication history, history of missions, and "new" institutional history. The author offers an overarching portrayal of the writing, printing, and circulation of books of 'Japano-martyrology.' The book is organized into two parts. The first part, "Spirituality of Writing, Publication History, and Japano-martyrology," addresses topics ranging from the historical background of Christianity in Japan to the publishers of Japano-martyrology. The second part, "Jesuits, Discalced Franciscans, and the Production of Japano-martyrology in the Early Modern Spanish World," features closer analysis of selected works of Japano-martyrology by Jesuit and Discalced Franciscan writers"--